Epidemiological Overview of African Swine Fever in Uganda (2001–2012). (12th August 2013) - Kalenzi Atuhaire, David; Ochwo, Sylvester; Afayoa, Mathias; Norbert Mwiine, Frank; Kokas, Ikwap; Arinaitwe, Eugene; Ademun-Okurut, Rose Anna; Boniface Okuni, Julius; Nanteza, Ann; Ayebazibwe, Christosom; Okedi, Loyce; Olaho-Mukani, William; et al.
Abstract : African swine fever (ASF) is a contagious viral disease, which can cause up to 100% mortality among domestic pigs. In Uganda there is paucity of information on the epidemiology of the disease, hence a study was carried out to elucidate the patterns of ASF outbreaks. Spatial and temporal analyses were performed with data collected monthly by the district veterinary officers (DVOs) and sent to the central administration at MAAIF from 2001 to 2012. Additionally, risk factors and the associated characteristics related to the disease were assessed based on semistructured questionnaires sent to the DVOs. A total of 388 ASF outbreaks were reported in 59 districts. Of these outbreaks, 201 (51.8%) were reported in districts adjacent to the national parks while 80 (20.6%) were adjacent to international borders. The number of reported ASF outbreaks changed over time and by geographical regions; however, no outbreak was reported in the North-Eastern region. ASF was ranked as second most important disease of pigs, and it occurred mostly during the dry season (P = 0.01 ). Pig movements due to trade (OR 15.5, CI 4.9–49.1) and restocking (OR 6.6, CI 2.5–17.3) were the major risk factors. ASF control strategies should focus on limiting pig movements in Uganda.